2004
DOI: 10.1002/sia.1875
|View full text |Cite
|
Sign up to set email alerts
|

XPS study of Cu/substrate systems obtained by pulsed laser deposition

Abstract: In this paper XPS was used to study the evolution of Cu 2p 3/2 peaks with the increase of the metal coverage on different types of substrate: Ni, HOPG (highly orientated pyrolytic graphite) and KBr. The results showed that: (i) the binding energy of the Cu 2p 3/2 peak in the system Cu/HOPG decreases with surface coverage, while in the system Cu/Ni it increases; (ii) with the increase of the Cu coverage in all the systems studied a general trend of the Cu 2p 3/2 peak is the reduction of FWHM (full width at half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…been discussed in terms of a final state effect, contrary to our conclusion. However the correlation energy shift has been neglected in the Auger parameter analysis of Lai et al [16]. If we would neglect the correlation energy shift than the final state effect would indeed be stronger than the initial state effect as readily inferred from Fig.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…been discussed in terms of a final state effect, contrary to our conclusion. However the correlation energy shift has been neglected in the Auger parameter analysis of Lai et al [16]. If we would neglect the correlation energy shift than the final state effect would indeed be stronger than the initial state effect as readily inferred from Fig.…”
Section: Resultsmentioning
confidence: 93%
“…1a. Lai et al [16] have measured a positive binding energy shift of atomic Cu-islands of various thicknesses on HOPG. This experimental observation, which is similar to ours, has Table 1 Binding energy shift BE (2p 3/2 ), Auger energy shift KE (peak maximum of L3M4,5M4,5) and Coulomb correlation energy shift of the 3d −2 Auger final state Ecorr [23] as derived from Ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparing the XPS spectra of Cu(OH) 2 @Ni(OH) 2 with pure Cu(OH) 2 and Ni(OH) 2 , it can be found that the characteristic peak is shifted, which is due to the strong interaction between Cu(OH) 2 and Ni(OH) 2, leading to the shift of the binding energies of Cu and Ni in Cu(OH) 2 @Ni(OH) 2 . [26][27][28] The electrochemical behavior of Cu(OH) 2 @Ni(OH) 2 electrode using mercury oxide (HgO) as reference electrode was investigated in a three-electrode system with the potential window of 0-0.5 V in 6 m KOH. In the meantime, Cu(OH) 2 @ Ni(OH) 2 testing electrode has been characterized by SEM to confirm the operating status after a battery of cyclic voltammogram (CV), galvanostatic charge and discharge (GCD), and electrochemical impedance spectroscopy (EIS) measurements, and the corresponding digital images are displayed in Figure S1a,b (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Considerable research studies were carried out to examine laser treatment of high‐performance nickel‐based alloys . Effect of heat treatment on microstructure and mechanical properties of laser‐treated Rene 41 was investigated by Li et al …”
Section: Introductionmentioning
confidence: 99%